PHARMACOECONOMIC EFFECTIVENESS OF NAFTIDROFURYL IN PATIENTS WITH ISCHEMIC STROKE - A. N. Bogolepova; D. Yu. Belousov; A. E. Cheberda (Klinicist)
The study objective is to conduct a pharmacoeconomic analysis of naftidrofuryl effectiveness in patients with ischemic stroke.Materials and methods. The work is based on the results of clinical studies of effectiveness, tolerability, and safety of naftidrofuryl in patients who suffered an ischemic stroke. The study design included data on 1000 patients of 45 and older with first-time acute cerebrovascular disease of ischemic type.Results. Direct medical costs for the chosen patient cohort per the Standard of stroke treatment current at the time of the study were 730 575 189 rubles, in case of naftidrofuryl inclusion they were 476 467 620 rubles. Cost minimization is 254 107 569 rubles. Indirect nonmedical costs associated with temporary incapacity for work for treatment per the Standard of stroke treatment were 124 156 950 rubles, and 64 559 180 rubles for naftidrofuryl use which demonstrates the drug’s economic benefit. Budget impact analysis has shown that the possible savings constitute 7.59 %.Conclusion. Inclusion of naftidrofuryl into treatment of patients with ischemic stroke is justified as it decreases duration of rehabilitation. This leads to a positive economic effect expressed as decreased direct and non-direct medical costs.